Pengaruh Struktur ModalL, Likuiditas dan Pertumbuhan Terhadap Kebijakan Deviden di BEI - Dewi, Ni Wayan Trisna; Sedana, Ida Bagus Panji (E-Jurnal Manajemen; Vol 3 No 6 (2014), 2014)
Dividend policy is a policy whether profits from the company will be distributed to shareholders as dividends or be retained in the form of retained earnings to finance investment in the future . Dividend policy is very important because investors wa n ted profits from the company to be distributed as dividends , but companies wanted profits from the company to be detained in order to finance investments and operations. Therefore, it is important to know what are the factors that affect dividend policy. This study aims to determine the effect of capital structure , liquidity , and growth of the company against company dividend policy . These results indicate that capital structure significantly and negatively related to the dividend policy . Liquidity positive and significant effect on dividend policy . The company's growth and a significant negative effect on dividend policy . . Keywords : capital structure , liquidity , growth, dividend policy . Normal 0 false false false EN-US X-NONE X-NONE
Keywords: capital structure , liquidity , growth, dividend policy .